Water flow and transport in porous media for in-silico espresso coffee. (May 2020) - Giacomini, Josephin; Khamitova, Gulzhan; Maponi, Pierluigi; Vittori, Sauro; Fioretti, Lauro
Highlights: Physico-chemical modelling of coffee extraction. Fluid flow in porous media. Transport of solutes and particles in porous media. In-silico coffee extraction. Abstract: Brewing coffee is primarily considered an art rather than a business. Drinking coffee is a practice spread worldwide irrespective of race, age, and social extraction, making coffee the leading commodity in the fair trade movement. Its daily consumption has scientifically proven health benefits. Thus, such interesting features of coffee have stimulated a wide coffee-oriented scientific research addressing health, social and economical aspects. An important component of this research is an in-depth knowledge of the physico-chemical processes occurring in the coffee preparation. In this paper, we propose a mathematical model for describing the percolation processes occurring during the espresso coffee extraction by exploiting fluid-dynamics components. The validity of this water percolation model into porous media is demonstrated on an experimental basis, exploiting chemical laboratory analyses of espresso coffee samples extracted under different conditions.